Labor market frictions, investment and capital flows - Clemens C. Struck (University College Dublin, UCD School of Economics, 2017)
The standard neoclassical model predicts that countries with higher productivity growth rates experience sharp increases in investment that are followed by rapid declines. This investment response contrasts with the empirical evidence that suggests a rather hump-shaped investment behavior. In this paper, I present a two-country general equilibrium model that generates hump-shaped investment responses from labor market frictions. In the model, I decompose investment into tradable and non-tradable components and show that an increase in the growth rate of a country results in scarcities of the non-tradable components which raise the relative price of investment goods. These scarcities occur because labor is unable to reallocate quickly between sectors within economies.
Keywords: F21; F32; 330; investment prices; capital flows; current account; global imbalances; capital returns; labor market frictions; trade frictions